(untitled) (Research, Society and Development, 2023)
Cholecystectomy is the most prevalent digestive tract surgery in the world. In Brazil, from 2015 to 2020, 1,167,754 cholecystectomies were performed. The objective of the study is to identify the prevalence and factors associated with mortality of patients undergoing cholecystectomy in a public hospital in southern Brazil from 2015 to 2020. All medical records of patients undergoing cholecystectomy at Hospital Governador Celso Ramos (HGCR) were analyzed. between January 2015 and December 2020, totaling 988 medical records. The most common demographic and clinical characteristics were female gender, age group over 50 years, previous history of systemic arterial hypertension, diabetes mellitus, cardiovascular disease and obesity. A total of 567 patients (63.0%) with comorbidities were identified. About 853 (88.8%) underwent SVC. The frequency of deaths was 0.81% (8 cases). It is concluded that the profile of patients found in this study requires multiprofessional monitoring for early diagnosis and treatment, as well as the need for training and expansion of adequate accessibility for the treatment of gallbladder calculi in the hospital environment.